Pendidikan Keagamaan Tahsin, Kegiatan Open Donasi dan Pendidikan Kebudayaan di Pondok Pesantren Al-Mubarok Bengkulu - Sutrian Efendi; Weni Wahyu Saputri; Bety Nurfadilah; Suris Marshanda; Hengki Satrisno; Reta Guspani (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Counseling and psychological support services play an important role in maintaining mental health, which affects the quality of life, social interaction, and resilience of individuals in facing challenges. This study aims to provide real experiences in community development through the MBKM KKN program, with a focus on the implementation of religious education, social activities, and cultural preservation at the Al-Mubarok Islamic Boarding School in Bengkulu. Tahsin education activities are an important part of improving the ability to read the Qur'an properly and correctly. In addition, the implementation of open donations reflects social participation that encourages the sustainability of Islamic boarding school programs. On the other hand, cultural education aims to instill local and national values ​​in students from an early age, as an effort to shape the identity and character of the nation. This study uses the Asset-Based Community Development (ABCD) approach, which utilizes local potential and assets as the basis for community development. The results show that the three aspects—tahsin education, social donations, and cultural learning—run synergistically and consistently. This collaboration contributes to the formation of the spiritual, social, and cultural character of students. The study recommends strengthening cooperation between Islamic boarding schools, the community, and donors to continuously improve the quality of education and welfare of students.